A qualitative study to explore the help-seeking views relating to depression among older Black Caribbean adults living in the UK. (17th February 2021) - Bailey, Natalie Victoria; Tribe, Rachel
Abstract: Numbers of older adults are rising globally. In the UK, rates of mental ill-health are thought to be higher in Black Asian and Minority Ethnic communities than in the white population. Older adults from BAME groups are an under researched group. It is important to understand the experiences and beliefs that underlie help-seeking behaviour among BAME older adults to deliver effective, culturally appropriate, and accessible services. This study aims to explore help-seeking views and strategies utilized in relation to depression among older Black Caribbean people in the UK. Semi-structured interviews were conducted with eight UK Black Caribbean participants, aged between 65 and 79 years. Transcripts were analysed using Interpretative Phenomenological Analysis. Three master themes emerged from the analysis: (1) 'If you don't know, you don't seek help', (2) 'I was depressed…I knew I was depressed', 3) 'You have to decide': Attitudes to help-seeking and mental health service use. Participants' past personal experiences of coping with depression, including migratory histories, cultural and religious views, and personal relationships influenced their help-seeking views and preferred coping methods for depression.